СУЩНОСТЬ И ОСОБЕННОСТИ ГУМАНИЗАЦИИ АКСИОЛОГИЧЕСКОГО ВОСПИТАНИЯ СТУДЕНТОВ - Утемуратова, Ю.М. (SCIENCE and SOCIETY, 2023)
The article analyzes the problem under study, shortcomings in the system of humanistic education; various ideas and directions in pedagogy have been widely studied and implemented: Karakalpak folk traditions; socio-cultural competence; humanistic ideas of Karakalpak folklore and literature; ethnopedagogy of the Karakalpak people; culture of the Karakalpaks.